Trust in medicine : its nature, justification, significance, and decline / Markus Wolfensberger, Anthony Wrigley. - Wolfensberger, Markus, 1948-; Wrigley, Anthony (Cambridge bioethics and law., 2019)
Over the past decades, public trust in medical professionals has steadily declined. This decline of trust and its replacement by ever tighter regulations is increasingly frustrating physicians. However, most discussions of trust are either abstract philosophical discussions or social science investigations not easily accessible to clinicians. The authors, one a surgeon-turned-philosopher, the other an analytical philosopher working in medical ethics, joined their expertise to write a book which straddles the gap between the practical and theoretical. Using an approach grounded in the methods of conceptual analysis found in analytical philosophy which also draws from approaches to medical diagnosis, the authors have conceived an internally coherent and comprehensive definition of trust to help elucidate the concept and explain its decline in the medical context. This book should appeal to all interested in the ongoing debate about the decline of trust - be it as medical professionals, medical ethicists, medical lawyers, or philosophers.